Adenoviral-vectored epigraph vaccine elicits robust, durable, and protective immunity against H3 influenza A virus in swine - Petro-Turnquist, Erika; Pekarek, Matthew; Jeanjaquet, Nicholas; Wooledge, Cedric; Steffen, David; Vu, Hiep; Weaver, Eric A. (Frontiers in Immunology, 2023)
Current methods of vaccination against swine Influenza A Virus (IAV-S) in pigs are infrequently updated, induce strain-specific responses, and have a limited duration of protection. Here, we characterize the onset and duration of adaptive immune responses after vaccination with an adenoviral-vectored Epigraph vaccine. In this longitudinal study we observed robust and durable antibody responses that remained above protective titers six months after vaccination. We further identified stable levels of antigen-specific T cell responses that remained detectable in the absence of antigen stimulation. Antibody isotyping revealed robust class switching from IgM to IgG induced by Epigraph vaccination, while the commercial comparator vaccine failed to induce strong antibody class switching. Swine were challenged six months after initial vaccination, and Epigraph-vaccinated animals demonstrated significant protection from microscopic lesion development in the trachea and lungs, reduced duration of viral shedding, lower presence of infectious virus and viral antigens in the lungs, and significant recall of antigen-specific T cell responses following challenge. The results obtained from this study are useful in determining the kinetics of adaptive immune responses after vaccination with adjuvanted whole inactivated virus vaccines compared to adenoviral vectored vaccines and contribute to the continued efforts of creating a universal IAV-S vaccine.